MRSA outbreak blamed on ﬂagrant overmedications - ORNAC, ORNAC (Operating Room Nurses Association of Canada Journal, 1987)
There are numerous reasons why slavish adherence to infection control procedures should be an avid and on-going concern to all operating room nursing personnel. An especially important reason, among others, is the the alarming ability of certain bacteria to develop resistances to antibiotics.